Advances in multi-photon processes and spectroscopy (World Scientific, 1986)
A text containing a selection of review articles on the following topics: quantum control of molecular dynamics, modern perspective on coherent control, molecular engineering of push-pull choromophores, time-resolved pumped sum-frequency generation spectroscopy, and related topics.